2019
DOI: 10.1021/acschembio.9b00113
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Protein Degradation through Cytosolic Delivery of Monobody Binders Using Bacterial Toxins

Abstract: Monobodies are small engineered binding proteins that, upon expression in cells, can inhibit signaling of cytosolic oncoproteins with outstanding selectivity. Efficacy may be further increased by inducing degradation of monobody targets through fusion to the von Hippel–Lindau (VHL) substrate receptor of the Cullin2-E3 ubiquitin ligase complex. However, potential therapeutic use is currently limited, because of the inability of monobody proteins to cross cellular membranes. Here, we use a chimeric bacterial tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Efforts to overcome the delivery challenge in the context of targeted protein degradation have primarily focused on viral delivery methods, although a recent study by our group demonstrated the potential of nanoplex‐mediated delivery of synthetic mRNA encoding uAbs to achieve highly efficient silencing in vitro and in vivo. 101 In another recent study, Hantschel and coworkers used a chimeric bacterial toxin to deliver uAbs in cancer cells . Although not yet demonstrated for protein‐based degraders, a number of other strategies have been described for internalizing intact proteins including the use of cationic lipids, cell‐penetrating peptides, covalent attachment of oligosaccharides, esterification, and polymeric nanoparticles …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to overcome the delivery challenge in the context of targeted protein degradation have primarily focused on viral delivery methods, although a recent study by our group demonstrated the potential of nanoplex‐mediated delivery of synthetic mRNA encoding uAbs to achieve highly efficient silencing in vitro and in vivo. 101 In another recent study, Hantschel and coworkers used a chimeric bacterial toxin to deliver uAbs in cancer cells . Although not yet demonstrated for protein‐based degraders, a number of other strategies have been described for internalizing intact proteins including the use of cationic lipids, cell‐penetrating peptides, covalent attachment of oligosaccharides, esterification, and polymeric nanoparticles …”
Section: Resultsmentioning
confidence: 99%
“…A distinct advantage of uAbs is their highly modular architecture which enables target selection to be rewired by simply swapping the synthetic protein‐binding domain. For example, targeted proteolysis has been achieved for a diverse array of protein substrates including eukaryotic proteins (ASC, HRAS/KRAS, Lck, and SHP2,), intraneuronal bacterial proteins ( Clostridium botulinum neurotoxin [BoNT] proteases), fluorescent proteins (FPs), and dozens of FP‐tagged proteins that range in size from 27 to 179 kDa and localize in different subcellular compartments including the cytoplasm, nucleus, and cell membrane . Moreover, by incorporating synthetic binding proteins that recognize particular protein states (e.g., active vs. inactive conformation, mutant vs. wild‐type, posttranslationally modified, and so forth), it becomes possible to deplete certain protein subpopulations while sparing others .…”
Section: Engineering Posttranslational Protein Degradation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumour imaging with monobodies conjugated to (B) radioisotopes [62] and (C) microbubbles [52]. (D) Targeted degradation of endogenous intracellular proteins [63] and (E) targeted intracellular fluorescence reporters for endogenous proteins [64].…”
Section: Delivery Agentsmentioning
confidence: 99%
“…Their high affinity, specificity and straightforward expression in multiple cell types also make them a versatile tool for research 6,31 . The small size and relative stability of monobodies (less than 100 amino acids), as well as their lack of disulfide bridges, robust activity inside 33 and outside of cells 34 , and their ability to be selected to bind countless different proteins with high affinity and selectivity, make them ideal candidates to develop light-switchable protein binders by fusing them to light-responsive proteins.…”
Section: Introductionmentioning
confidence: 99%